PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TGT MENGGUNAKAN CHEM CARD UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN HIDROKARBON DI KELAS X SMA NEGERI 10 PEKANBARU - Karmelina Karmelina '; Betty Holiwarni Betty Holiwarni; Miharty Miharty ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract: Research on the application of cooperative learning type of TGT using chem card to improve student achivement on the hydrocarbons subject at class X SMA Negeri 10 Pekanbaru was carried out in Mayth 2013. Purpose of this research was to determine whether the application of cooperative learning type of TGT using chem card can improve student achivement on hydrocarbons subject. This research is a design of experiment using a randomized control pretest-posttest. The sample consisted two classes of X7 as an experimental class and X5 as a control class. Experimental class with cooperative learning type of TGT using chem card and control class without TGT cooperative learning type of TGT using chem card. Analysis of the data that will be used is the t-test formula. The results of the data obtained tcount>ttable is 5,1923>1,67. It means that application of cooperative learning type of TGT using chem card can improve the student achivement on hydrocarbons subject at class X SMA Negeri 10 Pekanbaru with a percentage increase about 30,65%.Key words: Study achivement, Cooperative learning, TGT (Team Group Tournament), Chem card